2012
DOI: 10.1371/journal.pone.0040697
|View full text |Cite
|
Sign up to set email alerts
|

Male Yawning Is More Contagious than Female Yawning among Chimpanzees (Pan troglodytes)

Abstract: Yawn contagion is not restricted to humans and has also been reported for several non-human animal species, including chimpanzees (Pan troglodytes). Contagious yawning may lead to synchronisation of behaviour. However, the function of contagious yawning is relatively understudied. In this study, we investigated the function of contagious yawning by focusing on two types of signal providers: close social associates and leaders. We provided a captive chimpanzee colony with videos of all individuals of their own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 23 publications
4
81
1
1
Order By: Relevance
“…We used this control previously [13], and the effect sizes were even larger than when we used open mouth movements as a control [37]. Massen et al [38] also used this control and found a significant difference between yawn and control conditions. As no one has explicitly tested the performance of different controls against each other [44], we do not know whether any one control is better at eliciting baseline levels of yawning than any other (see [44] for a more in-depth discussion of controls used for studying CY).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used this control previously [13], and the effect sizes were even larger than when we used open mouth movements as a control [37]. Massen et al [38] also used this control and found a significant difference between yawn and control conditions. As no one has explicitly tested the performance of different controls against each other [44], we do not know whether any one control is better at eliciting baseline levels of yawning than any other (see [44] for a more in-depth discussion of controls used for studying CY).…”
Section: Methodsmentioning
confidence: 99%
“…To explore the origins of flexible empathy in humans, we studied the responses of one of our closest living relatives, the chimpanzee, in which CY is well established [13,19,20,[36][37][38]. Chimpanzees live in fission-fusion communities, which often compete [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…To date, experimental evidence of contagious yawning is restricted to humans (Homo sapiens; e.g., Provine 1986;Platek et al 2003), chimpanzees (Pan troglodytes) in response to conspecifics (Amici et al 2014;Anderson et al 2004;Campbell et al 2009;Campbell and de Waal 2011;Massen et al 2012) and human yawns (Campbell and de Waal 2014;; but see Amici et al 2014), domesticated dogs (Canis familiaris) in response to human yawns (Joly-Mascheroni et al 2008;Romero et al 2013;Silva et al 2012; but see Harr et al 2009;O'Hara and Reeve 2011;Buttner and Strasser 2014), and, most recently, a subline of high-frequency yawning Sprague-Dawley rats (Rattus norvegicus; Moyaho et al 2014). Video-induced yawning has also been reported in stumptail macaques (Macaca arctoides; Paukner and Anderson 2006), but this response also cooccurred with heightened self-directed behaviors and thus appears to be due to social tension or stress rather than contagion.…”
Section: Introductionmentioning
confidence: 99%
“…Contagious yawning has been observed in chimpanzees [38,39], gelada baboons [40], and dogs [41]. Dogs apparently may even be able to "catch" yawns from humans [42], and, in this case, dogs are more susceptible to yawning in response to yawns by familiarrather than unfamiliar persons [43].…”
Section: The Contagiousness Of Yawningmentioning
confidence: 99%
“…Gender plays a role in yawn contagion in certain animals, but not in humans. In a study of contagious yawning among chimpanzees, it was found that yawns from male chimps were more contagious than yawns from females; since males dominate in chimpanzee society, this suggests that yawning has a communicative function and that messages from males are more valued [38]. Yawns by male chimps were more contagious to both male and female chimps.…”
Section: The Contagiousness Of Yawningmentioning
confidence: 99%